Fundamentals of biodiversity - Klyachenko, O. L.; Lisovyy, M. M.; Kvasko, O.Yu. (My University, 2023)
The textbook contains basic theoretical information about the basic concepts of studying biodiversity, its classification, methods of assessment, and preservation. The indicated main threats and problems of today are related to the impoverishment of biodiversity. The textbook is aimed at familiarizing future specialists with the basic principles of monitoring, inventory of species diversity and wealth, analysis of primary information, etc. For students, postgraduates, teachers, and research staff of biological, ecological, and agricultural universities specializing in the field of biology, biotechnology and ecology, and environmental protection
Recommended for publication by decision of the academic council National University of Life and Environmental Sciences of Ukraine
Keywords: Біорізноманіття; Biodiversity